Telecom in India in 2017: Uncertainty Calling. Issue 2 (September 2020) - Jain, Ravi Kumar; Gonela, Saradhi Kumar; Raghavendra BT,
The Indian telecom industry, one of the fastest-growing markets in the world, was at crossroads. The industry grew in two decades by focusing primarily on reducing voice call charges. By the end of 2016, a new entrant disturbed the strategies of all the incumbents. Reliance Jio, the new competitor, disrupted the market by promising completely free voice calls—hitherto staple revenue stream for the incumbents—and undercut data price to approximately tenth of incumbents' prices. The resulting cacophony severely damaged the incumbents to the extent that Vodafone and Idea Cellular, the second and third largest incumbents, announced a merger. Airtel, the unchallenged market leader for more than 15 years, was bracing to face financial losses. The changed scenario posed several difficult questions to all the operators. Finding answers, though vital for existence, would prove to be a horrendous task. This case presents the students with the dilemma of how to face the new entrant, with unconventional strategies. This case will be ideal in the Business Strategy course.